Using Inquiry based module in chemistry laboratory work to enhance manipulative skills - Shuhimi, Rahayu Ezranie (2015)
This decade, science and technology education has been given specific attention all at academic level. Malaysia Education Blueprint 2013-2025 states that students must be equipped with the necessary skills to face the challenges of a changing with the application of Science, Technology, Engineering and Mathematics (STEM). This is to meet the need to provide students who competent effectively on a global level. Exposure to scientific skills such as manipulative skills at an early stage is one of the effective methods to provide young people with skills that are very important nowadays. Manipulative skills refer to the ability to use and handle science apparatus and substances correctly while doing an experiment in a laboratory. However, previous studies showing practical work in laboratory are still a host of ‘follow the recipe’ procedure without the involvement of mental framework or the development of higher-order thinking skills. In other words, the practical work is a 'hands-on' activities rather than 'minds-on'. Recognizing the importance of hands-on laboratory activities for learning science, an approach that is called inquiry based science education (IBSE) approach can help students effectively acquire science process skills. Therefore, this study was conducted to provide added value in teaching in the laboratory through the use of module based on inquiry based science education (IBSE) as it can be an important step to help students to improve the manipulative skills. As this study is at initial phase, in this paper, researcher will explain about the use of inquiry based module in chemistry laboratory work. Researcher hope that this study can contribute to future research on manipulative skills and inquiry based learning especially in chemistry laboratory environment.